1997
DOI: 10.1046/j.1365-2141.1997.1262940.x
|View full text |Cite
|
Sign up to set email alerts
|

Avascular necrosis of bone after allogeneic bone marrow transplantation: analysis of risk factors for 4388 patients by the Société Française de Greffe de Moëlle (SFGM)

Abstract: Increasing numbers of patients are surviving after allogeneic bone marrow transplantation and are therefore at risk for developing late complications. Among these complications, avascular necrosis of bone has been reported, but only two single‐centre studies included sufficient patients to enable analysis of the risk factors for developing avascular necrosis. In this multicentre retrospective study the aim was to assess risk factors for this complication in a large number of patients. The population consisted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
80
1
3

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(90 citation statements)
references
References 19 publications
6
80
1
3
Order By: Relevance
“…Other rare causes such as serum sickness 6 or prostaglandin E1-induced arthritis 7 have been described. A more common cause for arthralgia (without arthritis) in this setting, is avascular necrosis, 8 which is often due to chronic high-dose steroid therapy. In cases of infective arthritis, the causative agent is usually bacterial but can occasionally be viral.…”
Section: Discussionmentioning
confidence: 99%
“…Other rare causes such as serum sickness 6 or prostaglandin E1-induced arthritis 7 have been described. A more common cause for arthralgia (without arthritis) in this setting, is avascular necrosis, 8 which is often due to chronic high-dose steroid therapy. In cases of infective arthritis, the causative agent is usually bacterial but can occasionally be viral.…”
Section: Discussionmentioning
confidence: 99%
“…Onset of clinical symptoms starts once necrosis occurs in the cortical area. AVN may lead to significant morbidity and compromised quality of life with an incidence ranging from 4.3 39 to 19%. 40 Older age at transplant, acute and chronic GvHD, underlying disease and TBI are the main risk factors.…”
Section: Complications Affecting the Locomotor Apparatusmentioning
confidence: 99%
“…40 Older age at transplant, acute and chronic GvHD, underlying disease and TBI are the main risk factors. [39][40][41][42] In a recent Italian case-control paediatric study, the risk factors associated with AVN in a multivariate analysis were older age at HSCT, TBI and cGvHD. 43 Continuous and longer use of steroids after HSCT was, however, not associated with the risk of developing AVN, nor the cumulative doses used.…”
Section: Complications Affecting the Locomotor Apparatusmentioning
confidence: 99%
“…32 Older age at HSCT, acute and cGVHD, type of underlying disease (such as severe aplastic anaemia or ALL) and TBI are the main risk factors for avascular necrosis. 23,24,64 Univariate analysis alone showed that the continuous use of steroids after HSCT is a significant risk factor for avascular necrosis. 64 Pre-transplant screening for avascular necrosis by magnetic resonance imaging 52 is not recommended except in patients who have suspicious clinical signs for this complication, such as persistent bone pain.…”
Section: Risk Factors For Hepatic Toxicitymentioning
confidence: 99%